Neurofibromin C terminus-specific antibody (clone NFC) is a valuable tool for the identification of NF1-inactivated GISTs - Rossi, Sabrina; Reuss, David; Deimling, Andreas von (Modern pathology, 2018)
An increasing body of evidence supports the involvement of NF1 mutations, constitutional or somatic, in the pathogenesis of gastrointestinal stromal tumors (GISTs). Due to the large size of the NF1 locus, the existence of multiple pseudogenes and the wide spectrum of mechanisms of gene inactivation, the analysis of NF1 gene status is still challenging for most laboratories. Here we sought to assess the efficacy of a recently developed neurofibromin-specific antibody (NFC) in detecting NF1-inactivated GISTs. NFC reactivity was analyzed in a series of 98 GISTs. Of these, 29 were ‘NF1-associated’ (17 with ascertained NF1 mutations and 12 arising in the context of clinically diagnosed Neurofibromatosis type 1 syndrome and thus considered bona fine NF1 inactivated); 38 were ‘NF1-unrelated’ (either wild-type or carrying non-pathogenic variants of NF1). Thirty-one additional GISTs with no available information on NF1 gene status or with NF1 gene variants of uncertain pathogenic significance were also included in the analysis. Cases were scored as NFC negative when, in the presence of NFC positive internal controls, no cytoplasmic staining was detected in the neoplastic cells. NFC immunoreactivity was lost in 24/29 (83%) NF1-associated GISTs as opposed to only 2/38 (5%) NF1-unrelated GISTs (P=3e−11). NFC staining loss significantly correlated (P=0.007) with the presence of biallelic NF1 inactivation, due essentially to large deletions or truncating mutations. NFC reactivity was instead retained in two cases in which the NF1 alteration was heterozygous and in one case where the pathogenic NF1 variant, although homo/hemizygous, was a missense mutation predicted not to affect neurofibromin half-life. Overall this study provides evidence that NFC is a valuable tool for identifying NF1-inactivated GISTs, thus serving as a surrogate for molecular analysis.
Published online 1 September 2017
Im Titel ist "NF1" in NF1-inactivated kursiv geschrieben
Gesehen am 18.04.2019